THE EFFECT OF COLEUS TUBEROSUS CONTAINING RESISTANT STARCH TYPE 3 CRACKERS ON HYPERCHOLESTEROLEMIA SUFFERING ANIMALS - Nugraheni, Mutiara; Hamidah, Siti; Auliana, Rizqie (Jurnal Penelitian Saintek, 2017)
This study was aimed at determining the effect of Coleus tuberosus containing resistant starch type 3 on the hypercholesterolemia suffering animals. The research method used was lipid proï¬ le analysis on experimental animals suffering from hypercholesterolemia. The results showed that the consumption of Coleus tuberosus crackers containing resistant starch type 3 as a raw material for making crackers is able to decrease the lipid proï¬ le (total cholesterol, triglycerides, LDL) and increase the HDL level.